Peranan Fasilitator Pendamping Untuk Meningkatkan Pendapatan Dan Skill Nasabah Btpn Syariah Kec. Wiyung Dalam Berwirausaha - Andramaya Kusuma Ningtyas; Siti Ning Farida (Jurnal Akuntan Publik, 2024)
The economy in Indonesia is starting to experience an increase in income. It can be seen today that many people choose to become entrepreneurs. PT Bank BTPN Syariah Tbk carries out the "Bestee" internship program with business assistance for underprivileged customers. In this program, BTPN Syariah attracts participants from the Certified Independent Study and Internship (MSIB) program. This research aims to see how influential the role of BTPN Syariah customer business assistance is on increasing customers' income and skills in entrepreneurship. The method used in this research is a descriptive method with a qualitative approach. The business assistance carried out by this facilitator has a good effect on BTPN Syariah customers who run MSMEs where they can improve soft skills and good hard skills regarding entrepreneurship that have never been known before, increase sales income significantly due to the material provided during mentoring and can effectively increase performance of MSMEs run by BTPN Syariah underprivileged customers.